Orofacial pigmentary lesions in the pediatric age group: A descriptive observational study - Neerja Saraswat; Ajay Chopra; Sushil Kumar; Shekhar Neema; Parul Kamboj (Wolters Kluwer Medknow Publications, 2020)
Background: Pigmentary disorders on the face are frequently encountered in all age groups and both genders but are more common in pediatric patients. These lesions can be isolated incidental findings or indicative of a congenital or acquired systemic or genetic disorder. Aims and Objectives: The aim and objective of this study is to study the frequency and pattern of pigmented orofacial lesions in the pediatric age group and to describe the underlying associated condition if any. Materials and Methods: A descriptive study was conducted over a period of 6 months (June-November 2018) in the dermatology department of a tertiary care hospital in Eastern Uttar Pradesh. All the children from 2 to 14 years of age who reported to us with complaints of pigmentary lesions on the face or oral cavity were included, and attempt was made to find out if any underlying conditions. Results: A total of 207 children were included in the study. Pityriasis alba was the most common pigmentary disorder on the face in the study population in 146 (70.5%) children, while pityriasis versicolor was noted in 21 (10.1%). Other facial dermatoses noted were vitiligo, congenital melanocytic nevus, and postinflammatory hypopigmentation and hyperpigmentation. Eight (3.8%) children had associated underlying diseases such as xeroderma pigmentosum, dyskeratosis congenita, Vitamin B12 deficiency, Laugier-Hunziker syndrome, and juvenile dermatomyositis. Conclusions: Pigmentary disorders of the face and oral cavity are frequently seen in children which forms a major part of dermatology consultation. Although most of these disorders are of cosmetic concerns, few conditions are associated with systemic conditions. A thorough investigation and management are the keys to manage such cases.